MULTISLICE COMPUTED TOMOGRAPHY IN THE DIAGNOSIS OF MIXED TRAUMATIC BRAIN INJURY - A. V. Semenov; N. V. Monakov; E. I. Balkhanova; A. A. Raznobarskiy; T. A. Mamonova (Вестник рентгенологии и радиологии)
Objective: to study changes in the cross sectional optic nerve diameter (OND), by using multislice computed tomography (MSCT), in patients with mild traumatic brain injury  (TBI), as well as those with severe (including mixed) TBI before and  after craniotomy; to assess whether this technique can be integrated with a whole-body MSCT protocol in severe mixed TBI (MTBI).Material and methods. OND was retrospectively studied in two  selected groups of patients with injuries (a total of 51 patients):  Group 1 (n = 40) included 2 subgroups (n = 20 in each) with mild  TBI or severe MTBI; Group 2 (n = 11) comprised 2 subgroups with  severe TBI who had undergone decompressive (n = 6) or  osteoplastic (n = 5) craniotomy with subsequent OND measurement  after 12–18 hours. Results. Primary brain MSCT showed that the average OND was  6.12±1,01 mm in severe MTBI and 4.4±0.19 mm in mild TBI (Student’s t = 5.707). After decompressive craniotomy, there  was a decrease in OND from 6.26±0.27 to 5.38±0.22 mm (Student’s t = 2.486).Conclusion. Among the patients with severe MTBI, the OND at  primary MSCT is significantly greater than that in patients with mild  TBI, which may be due to elevated intracranial pressure, as shown  by the literature data. There is a statistically significant decrease in  OND after decompressive craniotomy and removal of the brain  compressive factor. Whole-body MSCT revealed no technical  obstacles to the application of an OND measurement technique.